Evaluation of isolates of Trichoderma, pseudomonas and bacillus species as treatment for the control of post-harvest fungal rot disease of yam (Dioscorea spp.) - Dania, V.O.; Fadina, O.O.; Ayodele, M.; Kumar, P. Lava (Informa UK Limited, 2016)
The efficacy of four biological control agents (BCAs): Trichoderma asperellum strain NGT158, T. longibrachiatum strain NGT167, Bacillus subtilis and Pseudomonas fluorescens for the management of post-harvest tuber rot among four yam species, Dioscorea rotundata, D. cayenensis, D. alata, and D. dumetorum was evaluated. Rotted yam tubers were collected across three agroecological zones in Nigeria to isolate six infecting fungal pathogens: Aspergillus niger, Lasiodiplodia theobromae, Rhizoctonia solani, Penicillium oxalicum, Fusarium oxysporum and Sclerotium rolfsii. The BCAs were isolated by serial dilution and rot inhibition of treated tubers was evaluated using destructive sampling method in vivo after six months of storage. Bacillus subtilis was generally most effective, especially when applied 24 h before the inoculation of test pathogens across the four yam species, with percent inhibition that ranged between 47.8 and 81.2%. However, the four BCAs showed good potential in the control of the fungal pathogens causing post-harvest yam rot.